1977
DOI: 10.1111/j.1469-8137.1977.tb02161.x
|View full text |Cite
|
Sign up to set email alerts
|

Stem Elongation in Tulip and Narcissus: The Influence of Floral Organs and Growth Regulators

Abstract: SUMMARY Decapitation of tulips early in extension growth resulted in a 59% reduction in stem length at flowering. Selective removal of the floral parts showed that the gynoecium controlled stem extension. The upper internodes were most affected, and the effect was largely reversed by the application of indol‐3‐ylacetic acid (IAA) but not by gibberellic acid (GA). Soil drenches of ancymidol also reduced tulip stem extension, but in this case the lower internodes were most affected and this effect was reversed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

1981
1981
2016
2016

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 18 publications
0
23
0
1
Order By: Relevance
“…5). A similar effect of flower stalk growth inhibition upon bud decapitation or emasculation was observed in the miniature Cymbidium orchid (Ohno and Kako 1991), the tulip (Hanks and Rees 1977;Saniewski and De Munk 1981), and the daffodil (Edelbluth and Kaldewey 1976;Hanks and Rees 1977).…”
Section: Impact On Peduncle Elongation and Vascular Anatomymentioning
confidence: 53%
See 2 more Smart Citations
“…5). A similar effect of flower stalk growth inhibition upon bud decapitation or emasculation was observed in the miniature Cymbidium orchid (Ohno and Kako 1991), the tulip (Hanks and Rees 1977;Saniewski and De Munk 1981), and the daffodil (Edelbluth and Kaldewey 1976;Hanks and Rees 1977).…”
Section: Impact On Peduncle Elongation and Vascular Anatomymentioning
confidence: 53%
“…It is in agreement with results obtained on Cymbidium flowers (Ohno and Kako 1991), which suggested that the peduncle is supplied mostly by auxins from the developing flower buds, especially from the anthers. Furthermore, selective removal of the floral parts in tulip and narcissus showed that gynoecium controls stem extension (Hanks and Rees 1977).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Auxins play a major role in controlling plant growth and are produced in areas of rapid cell (Hanks & Rees 1977). Stem treatments which significantly reduced secondary tuber production in sandersonia were pruning, tipping plus flower removal, and tipping plus pruning 4 weeks later.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these developmental constrains, environmental cues are interfering regularly with cut flower production. For example, floral bud blasting caused by high temperature during development in spring and summer has been occurring more frequently over the last decade ( Fig.1A-B) (Hanks and Rees, 1977). These high temperatures coincide with climate change and can lead to reoccurring events of floral bud blasting in the future, especially when these sensitive cultivars are used for breeding purposes.…”
Section: Introductionmentioning
confidence: 99%